Insights into the Category of Gender (with special reference to gender-marking avoidance strategies) - Karapetyan, Lili; Danukhyan, Lusine (Armenian Folia Anglistika, 2020)
Gender is an issue that has long preoccupied linguists, and the category of gender is one of the still unsolved puzzles of linguistic science. There has never been a complete agreement between scientists with regard to gender origin, nor there is unanimity of opinion as to its function in different language systems and, in general, to its definition. The present study focuses on the origin and historical development of the category of gender, classification of languages according to gender types, the peculiarities of gendered and genderless languages, gender-marking avoidance strategies. Through the comparative method of analysis English and Armenian gender systems are compared with an aim to reveal the similarities and differences in terms of functions, gender indicators in proverbs, as well as types of reference.
Keywords: category of gender; gender systems; gendered and genderless languages; gender-marking avoidance strategies